Comparative Effect of MSC Secretome to MSC Co-culture on Cardiomyocyte Gene Expression Under Hypoxic Conditions in vitro - Kastner, Nina; Mester-Tonczar, Julia; Winkler, Johannes; Traxler, Denise; Spannbauer, Andreas; Rüger, Beate M.; Goliasch, Georg; Pavo, Noemi; Gyöngyösi, Mariann; Zlabinger, Katrin (Frontiers in Bioengineering and Biotechnology, 2020)
Introduction Despite major leaps in regenerative medicine, the regeneration of cardiomyocytes after ischemic conditions remains to elucidate. It is crucial to understand hypoxia induced cellular mechanisms to provide advanced treatment options, including the use of stem cell paracrine factors for myocardial regeneration. Material and Methods In this study, the regenerative potential of hypoxic human cardiomyocytes (group Hyp-CMC) in vitro was evaluated when co-cultured with human bone-marrow derived MSC (group Hyp-CMC-MSC) or stimulated with the secretome of MSC (group Hyp-CMC-SMSC). The secretome of normoxic MSC and CMC, and the hypoxic CMC was analyzed with a cytokine panel. Gene expression changes of HIF-1α, proliferation marker Ki-67 and cytokinesis marker RhoA over different reoxygenation time periods of 4h, 8h, 24h, 48h and 72h were analyzed in comparison to normoxic CMC and MSC. Further, the proinflammatory cytokine IL-18 protein expression change, metabolic activity and proliferation was assessed in all experimental setups. Results and Conclusion HIF-1α was persistently overexpressed in Hyp-CMC-SMSC as compared to Hyp-CMC (except at 72 h). Hyp-CMC-MSC showed a weaker HIF-1α expression than Hyp-CMC-SMSC in most tested time points, except after 8 h. The Ki-67 expression showed the strongest upregulation in Hyp-CMC after 24h and 48h incubation, then returned to baseline level, while a temporary increase in Ki-67 expression in Hyp-CMC-MSC at 4h and 8h and at 48h in Hyp-CMC-SMSC could be observed. RhoA was increased in normoxic MSCs and in Hyp-CMC-SMSC over time, but not in Hyp-CMC-MSC. A temporary increase in IL-18 protein expression was detected in Hyp-CMC-SMSC and Hyp-CMC. Our study demonstrates timely dynamic changes in expression of different ischemia and regeneration-related genes of CMCs, depending from the culture condition, with stronger expression of HIF-1α, RhoA and IL-18 if the hypoxic CMC were subjected to the secretome of MSCs.